2018
DOI: 10.14202/vetworld.2018.965-970
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic preconditioning effect on stromal cells derived factor-1 and C-X-C chemokine receptor type 4 expression in Wistar rat's (Rattus norvegicus) bone marrow mesenchymal stem cells (in vitro study)

Abstract: Aim:To examine the effect of hypoxic preconditions on the ability of bone marrow stem cells culture mediated expression C-X-C chemokine receptor type 4 (CXCR4) and stromal cells derived factor-1 (SDF-1) in vitro.Materials and Methods:Bone marrow mesenchymal stem cells (BMSCs) were derived from 12 femurs of 200 g Wistar male rats. The animals were euthanized before BMSCs isolation. BMSCs were divided into two groups, control group: Normoxic condition 21% O2 and treatment group: Hypoxic condition 1% O2. The char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The results showed that 1% hypoxic preconditioning treatment significantly increased CXCR4 and SDF-1 expression, which play an important role in increasing the ability of MSCs to migrate to the damaged area and induce endogenous stem cells to proliferate and differentiate into the desired cells. 9 Thus, it is expected that there will be a process of improving the microenvironment of the resident stem cells, which will eventually lead to the regeneration process. In this study, transplantation of adaptive MSCs was administered by direct injection into salivary glands of Wistar rats damaged by exposure to 15 Gy of single dose ionizing radiations.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that 1% hypoxic preconditioning treatment significantly increased CXCR4 and SDF-1 expression, which play an important role in increasing the ability of MSCs to migrate to the damaged area and induce endogenous stem cells to proliferate and differentiate into the desired cells. 9 Thus, it is expected that there will be a process of improving the microenvironment of the resident stem cells, which will eventually lead to the regeneration process. In this study, transplantation of adaptive MSCs was administered by direct injection into salivary glands of Wistar rats damaged by exposure to 15 Gy of single dose ionizing radiations.…”
Section: Discussionmentioning
confidence: 99%
“…The specific ligand for the CXCR4 chemokine receptor is termed matrix-derived factor-1 (SDF-1, also known as CXCL12). Both CXCR4 and SDF-1 are expressed in various tissues and cell types and regulate cell migration [47]. The SDF-1/CXCR4 axis is also involved in the migration of CSCs [48].…”
Section: The Role Of Lscs In Tumor Metastasis and Invasionmentioning
confidence: 99%